计算:(x-4y)(2x+3y)-(x+2y)(x-y).
3个回答
( x-4y)(2x+3y)-(x+2y)(x-y)
=(2x2-5xy-12y2)-(x2-xy-2y2)
=x2-4xy-10y2
相关问题
计算(2x-3y)(x+4y)-(3x+y)(x-2y)
计算:(x-y)^2*(x+y)^3*(-x-y)^3*(y-x)^4
计算【3(x-y)^2(x+y)^-2/4(x+y)^2(x-y)^-2】^-2
(1) (3x-2y)(y-3x)-(2x-y)(3x+y) (2) (3x+2y+4)(5x-2y-1) 计算
计算:[(2x+3y)^2-2x(2x+3y)]/(-4y)
计算(x^2-y^2)/(x+y)-[4x(x-y)x+y^2]/2x-y
-2x^2y(3x^3y^2-4x^3y^2-4x^2y^2-3xy)计算
分式计算(x-y-4y^2/x-y)(x+y-4x^2/x+y)=?
计算:[(x+y/x-y)^2·(2y-2x/3x+3y)]-[(x^2/x^2-y^2)/(x/y)]
计算(-x-2y)∧2-(x-y+3)(x+y-3)-(2y-x)(x+3y),